ijee 2022
DOI: 10.48165/ijee.2022.58434
|View full text |Cite
|
Sign up to set email alerts
|

Constraints in Adoption of Laser Land Levelling Technology in Haryana

Abstract: The study analyzed perceptions of farmers about laser land levelling and constraints faced by them in adoption of this resource conservation technology in Sirsa and Karnal district of Haryana. Mean percent score tool of statistics was used to rank perceptions and constraints of farmers. It was noticed that 97.00 per cent respondent farmers believed that there is reduction in irrigation cost. 80.00 per cent believed that laser land levelling adoption helped in better weed management. Also, it was examined that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The perceptions of the farmers for the possible benefits of laser land levelling varied which caused the varied rate of its adoption by farmers (Larson et al, 2016). Kumar et al, (2022) also found that a large number of farmers assumed that it helped in reduction of irrigation cost and better fertilizer use efficiency in Sirsa and Karnal districts of Haryana.…”
Section: Adoption Of Climate-resilient Technologiesmentioning
confidence: 99%
“…The perceptions of the farmers for the possible benefits of laser land levelling varied which caused the varied rate of its adoption by farmers (Larson et al, 2016). Kumar et al, (2022) also found that a large number of farmers assumed that it helped in reduction of irrigation cost and better fertilizer use efficiency in Sirsa and Karnal districts of Haryana.…”
Section: Adoption Of Climate-resilient Technologiesmentioning
confidence: 99%